PERTANGGUNGJAWABAN NOTARIS/PPAT TERHADAP PENYALAHGUNAAN WEWENANG ATAS PEMBAYARAN BEA PEROLEHAN HAK ATAS TANAH (BPHTB) (Studi Putusan Pengadilan Negeri Surabaya Nomor 210/Pid. B/2022/PN SBY) - Wijaya, Eveline (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Notary/PPAT in practice often become intermediaries for depositing BPHTB payments to facilitate the transaction process, but some Notaries/PPATs often abuse their authority and power in the payment of BPHTB Tax. This type of research is Normative Juridical. Based on the results of the discussion in this paper that the responsibility of Notary / PPAT is that it should carry out its duties or authority properly and firmly without deviating from the applicable rules regarding its position, the legal consequences borne by Notary / PPAT who abuse the authority to pay BPHTB are subject to applicable sanctions. The conclusion of this discussion is that the Notary / PPAT is responsible for assisting the client's BPHTB payment instead of abusing his authority by using the client's BPHTB payment money for his personal needs so that the client and the state lose, the legal consequences received by the Notary / PPAT who abuses the authority are subject to criminal sanctions and compensation for the client who is harmed.